Multivariate association of wood basic density with site and plantation variables in Eucalyptus spp. - Ribeiro, Maria Dolores Dos Santos Barzotto [UNESP]; Rodrigues, Sergio Augusto [UNESP]; Ballarin, Adriano Wagner [UNESP] (Canadian Science Publishing, 2020)
Wood density, an important parameter for evaluating forest biomass productivity and wood product quality control, is influenced by a complex combination of variables of forest plantations, including environmental conditions and the management practices adopted. In this paper, we demonstrate that three site variables (annual rainfall, temperature, and soil texture) and 10 plantation variables (e.g., age and genetic material) are associated with basic wood density (evaluated in two situations: with and without bark) in 936 trees of different species of Eucalyptus L’Hér across five distinct edaphoclimatic regions in Brazil. A canonical correlation analysis was used to identify the most contributory variables affecting wood density. The variables globally associated with high basic wood densities were, in order of importance, the genetic material and area per tree (both under direct control of plantation managers), as well as mean annual temperature and soil texture of the site. These results confirmed the advantage of using clonal material (instead of seedling origin material) planted in larger spacings in sites with higher mean annual temperatures and clayey soils to obtain higher basic wood densities. Conversely, low basic wood densities were associated with high-productivity sites, higher rainfall, and plantations with a higher basal area per stem in second rotation.
Keywords: Canonical correlation analysis; Climatic variables; Eucalyptus spp.; Plantation variables; Wood density